Analysis of Moral Reasoning of Teachers and the Students with Respect to Kohlbergs Theory of Moral Development - Hafeez, Muhammad; Tahira, Fatima; Kazmi, Qaiser Abbas; Hussain, Muhammad Zahid (International Journal of Business Strategy and Social Sciences, 2020)
Moral development of persons is a basic aim of education. According to Islamic teachings success and failure of a person is judged on moral basis in this world and the hereafter. This study focuses on analysis of moral reasoning of teachers and the students with respect to Kohlberg’s theory of moral development. The target population for this study were teachers and students of secondary schools of district Dera Ghazi Khan. Twenty secondary schools were randomly selected from district Dera Ghazi Khan. Three (03) teachers and ten (10) students from each school were selected using random sampling method. The total sample size was 60 teachers and 200 students. Data was selected by DIT (defining issue test). The collected data was analyzed through descriptive analysis and chi-square test applied using SPSS. The results revealed that the participants reasoned predominantly at the conventional level of Kohlberg's moral reasoning which found that there is no significant difference between the view of teachers and students towards moral reasoning.